Analisis pengaruh penambahan rempah dan waktu simpan terhadap pH, kekentalan, serta kualitas organoleptik susu pasteurisasi - Ega Zahrotun Nisa; Angela Nitia Nefasa; Zakaria Husein Abdurrahman (Agroindustrial Technology, University of Trunojoyo Madura, 2022)
The purpose this study was on determine the effect an interaction between herbs additional and storage time on pH, viscosity, and organoleptic quality pasteurized milk. The primary raw materials in this study were cow fresh milk and herbs (ginger, cinnamon, turmeric). The low-temperature long time pasteurization was used at 63 °C for 30 minute, before the temperature 63 °C. The addition herbs is carried out when the milk temperature is 40 °C. The factors used in the pH and viscosity tests were the addition herbs as factor A and storage time (8 hours, 16 hours, and 24 hours at 23 °C) as factor B. The research design for testing pH and viscosity was a completely randomized design with a 2 x 3 with four repetitions. Meanwhile, for organoleptic testing, the completely randomized design pattern is in the same direction with 25 repetitions. The factor used is the addition herbs on pasteurized milk (factor A). There is an interaction between the addition seasoning and storage time can be lower the pH value and increase the viscosity (P0.01). The inuences the organoleptic quality showed that the addition herbs could affect (color, taste, and smell) which showed significant inuence (P0.01). The study concluded an interaction between the addition herbs and storage time on milk quality, as indicated by the pH the milk reprimarying at a good number after 8 hours storage at room temperature. The lower the pH value and the higher the viscosity, the longer the storage time. Herbs can affect the organoleptic quality (color, taste, and scent) pasteurized milk.